Smart Branding “Pesona Buaya” in Facilitating Business Identification Number (NIB) Management for MSMEs in Surabaya City - Andhika Akbar Ramadhan; Binti Azizatun Nafi’ah (Journal of Governance and Social Policy, 2025)
This study aims to analyze the implementation of smart branding by the "PESONA BUAYA" program in facilitating the registration of Business Identification Numbers (NIB) for Micro, Small, and Medium Enterprises (MSMEs) in Surabaya. This research employs a descriptive qualitative method using the Smart Branding Theory which focuses on three dimensions: trade, investment, and creativity. Smart branding is considered a crucial strategy for positively impacting business legality, which in turn can drive local economic growth. The data analysis technique used in this study follows the approach of Miles & Huberman (2015) to explore how smart branding positively influences the number of registered NIBs, with a particular focus on business branding. The findings of this study indicate that the "PESONA BUAYA" program significantly facilitates the legal registration process for businesses, leading to a positive increase in the number of NIBs in Surabaya, as evidenced by the continuous yearly growth in registration data. The results of this research are expected to contribute to the development of effective branding strategies in the context of public service and MSME empowerment.